Workplace Safety Concerns among Co-workers of Responder Returning from Ebola-Affected Country - Benjamin P. Chan; Elizabeth R. Daly; Elizabeth A. Talbot (Emerging Infectious Diseases, 2015)
We surveyed public health co-workers regarding attitudes toward a physician who returned to New Hampshire after volunteering in the West African Ebola outbreak. An unexpectedly large (18.0%) proportion of staff expressed discomfort with the Ebola responder returning to work. Employers should take proactive steps to address employee fears and concerns.